2023
DOI: 10.1128/jvi.00225-23
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Intrinsic CD38 Expression Sustains Exhausted CD8 + T Cells by Regulating Their Survival and Metabolism during Chronic Viral Infection

Abstract: Our study shows how CD38 expression is regulated on CD8 + T cells responding during acute and chronic viral infection. We observed higher CD38 levels on CD8 + T cells during chronic viral infection compared to levels during acute viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
2
5
1
Order By: Relevance
“…However, the study, in contrast to our findings, showed that CD38 deletion in LCMV-specific CD8 + T cells resulted in a modest but significant decrease in the frequency of TCF1 + Tpex cells during chronic LCMV Cl13 infection ( 38 ). We propose that the reduced frequency of TCF1 + P14 + T cells upon CD38 deletion may not be attributed to the decreased expression of TCF1 but instead to increased proliferation and subsequent differentiation of TCF1 + Tpex cells into highly effector TCF1 - PD1 + Tex cells, as observed earlier in the case of chronic LCMV infection ( 12 , 38 , 39 ). Therefore, it is possible that CD38 −/− LCMV-specific P14 + T cells, compared to wild-type P14 + T cells, had high TCF1 expression on a per-cell basis, triggering their massive expansion and differentiation into the effector subset upon antigen encounter in mice, while maintaining a small pool of TCF1 + P14 + T cells ( 12 , 39 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the study, in contrast to our findings, showed that CD38 deletion in LCMV-specific CD8 + T cells resulted in a modest but significant decrease in the frequency of TCF1 + Tpex cells during chronic LCMV Cl13 infection ( 38 ). We propose that the reduced frequency of TCF1 + P14 + T cells upon CD38 deletion may not be attributed to the decreased expression of TCF1 but instead to increased proliferation and subsequent differentiation of TCF1 + Tpex cells into highly effector TCF1 - PD1 + Tex cells, as observed earlier in the case of chronic LCMV infection ( 12 , 38 , 39 ). Therefore, it is possible that CD38 −/− LCMV-specific P14 + T cells, compared to wild-type P14 + T cells, had high TCF1 expression on a per-cell basis, triggering their massive expansion and differentiation into the effector subset upon antigen encounter in mice, while maintaining a small pool of TCF1 + P14 + T cells ( 12 , 39 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Congruently, we also observed that the dysfunctionality of Tex cells, in terms of their cytokine production, could partially be rescued by blocking CD38, suggesting the role of CD38 in regulating the functional fate of the T cells ( 17 ). The role of CD38 in regulating effector cytokine production by Tex has also been demonstrated in mice with chronic LCMV infection ( 38 ). However, the study, in contrast to our findings, showed that CD38 deletion in LCMV-specific CD8 + T cells resulted in a modest but significant decrease in the frequency of TCF1 + Tpex cells during chronic LCMV Cl13 infection ( 38 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to PDCD1 (encoding PD-1) and ENTPD1 (encoding CD39), the CD38 locus is open in exhausted T cells in cancer and chronic viral infection 13,43 . Interestingly, studies in patients with hepatitis C virus (HCV) confirmed high expression of CD38 in the setting of chronic viral infection, and demonstrated normalisation of CD38 expression following effective antiviral therapy 44,45 , in contrast to ENTPD1 and PDCD1 whose elevated expression is maintained even after successful viral clearance, suggesting permanent epigenetic scarring 40 . Thus, despite the strong co-expression of CD38 with PDCD1 (PD-1), ENTPD1 (CD39), and other putative exhaustion markers, the factors governing up- and -downregulation of CD38 and extent of reversibility will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, HLA-DR + CD8 + T-cells might have regulatory functions and express exhaustion markers. A recent study in mice showed that CD38 + CD8 + T-cells present during an acute or chronic infections can also expressed the exhaustion marker PD-1 and that CD38 expression, especially during a chronic CMV infection, lowered Granzyme B production and proliferation of the T-cells while supporting survival of these cells 27 . Potentially, the role of these HLA-DR + and/or CD38 + T-cells is to suppress immune responses during chronic infection.…”
Section: Discussionmentioning
confidence: 99%